SELECTED LEGAL ASPECTS RELATING TO A PATIENT’S RIGHT TO ACCESS MEDICAL RECORDS - Jacek, Anna; Porada, Sławomir (Review of European and Comparative Law, 2017)
The right to access medical records is one of the most important patient’s right. This right has been regulated in a number of legal acts, and in particular, in the provisions of the Act of November 6, 2008 on patient rights and the Patients Ombudsman1. The aim of the paper is to present selected legal aspects relating to patient right to access medical records. The provisions of the Act of November 6, 2008 on patient rights and the Patients Ombudsman define the obligation to respect the right to access medical records. However, it should be noted that most of the doubts concern the right to access medical records after the death of a patient, which is only available to a person authorized by the patient during his life. This causes that immediate family members do not have the right to access the patient’s medical records after his death, if they have not been authorized by him.